Ударное деформирование тонкостенной конструкции - Автономова, Людмила Владимировна; Бондарь, Сергей Владимирович; Степук, Александр Владимирович; Хавин, Валерий Львович; Шергин, Сергей Юрьевич (НТУ "ХПИ", 2016)
Проведено конечноэлементное моделирование процесса ударного деформирования тонкостенной конструкции из алюминиевого сплава при ударе пробойником с конусообразной формой рабочей части. Решение динамической контактной вязкопластической задачи позволило определить поля напряжений и деформаций для конструкции с дополнительным ребром жесткости. Анализ полей деформаций показал, что наличие дополнительного ребра приводит к перераспределению поля напряжений и приводит к увеличению жесткости всей конструкции.

The punch with cone-shaped working part impact into aluminum alloy thin-walled structures is mathematical modelled applying thermo-mechanical coupling of the physical processes during their deformation. The nonlinear physical properties contain a nonlinear stress-strain rate dependence of temperature. To solve the contact problem the sliding boundary conditions (friction) on moving bodies introduced. Numerical simulation of impact process performed using the finite element method and the independent Lagrange-Euler approach for two variants of the thin-walled box structure.The solution of the dynamic viscous plastic contact problem allowed to determine and to design the stress-strain fields in the thin-walled box section. For comparison, the deformation process of the similar aluminum construction with anadditional rib considered when the punch with the conical working part impact. Analysis of stress-strain state for two various types of structural geometries demonstrated that mounting the additional medial rib into its design let redistribute the stress fields and significantly reduce the plastic deformation area during the impact because of four fold increasing in its contact stiffness. Such modification of the structure rigidity may improve the strength properties of the entire composite security device applying changes only to its part.
High-speed deformation of a high-strength coated thin plate
Keywords: конструкция тонкостенная; удар; пробойник; задача контактная; метод конечных элементов; thin-walled structures; kick piercer; punch; contact problem; finite element method